Social Rejection and Alcohol Use in Daily Life. (2nd March 2017) - Laws, Holly B.; Ellerbeck, Nicole E.; Rodrigues, Alyne S.; Simmons, Jessica A.; Ansell, Emily B.
Abstract : Background: Prior studies have found that social rejection is associated with increases in negative affect, distress, and hostility. Fewer studies, however, have examined the impact of social rejection on alcohol use, and no known studies have tested whether the impact of social rejection by close others differs from social rejection by acquaintances in its association with subsequent drinking. Methods: Participants completed event‐contingent reports of their social interactions and alcohol use for 14 consecutive days on smartphones. Multilevel negative binomial regression models tested whether experiencing more social rejection than usual was associated with increased drinking, and whether this association was stronger when participants were rejected by close others (e.g., friends, spouses, family members) versus strangers or acquaintances. Results: Results showed a significant interaction between social rejection and relationship closeness. On days characterized by rejection by close others, the likelihood of drinking significantly increased. On days characterized by rejection by acquaintances, by contrast, there was no increase in the likelihood of drinking. There was no main effect of rejection on likelihood of drinking. Conclusions: These results suggest that relationship type is a key factor in whether social rejection translates to potentially harmful behaviors, such as increased alcohol use. This finding is in contrast to many laboratory paradigms of rejection, which emphasize rejection and ostracism by strangers rather than known others. In the more naturalistic setting of measuring social interactions on smartphone in daily life, our findings suggest that only social rejection delivered by close others, and not strangers, led to subsequent drinking. Abstract : Social rejection predicts increased drinking when rejected by close others (spouses, family members, close friends) but not when rejected by strangers or acquaintances. There was no significant difference between experiencing less rejection than usual by close others versus strangers (left side of the figure). On days where participants experienced greater than usual social rejection, however (right side of the figure), increased rejection by close others was associated with increased drinking, whereas increased rejection by strangers had no association with drinking.